2012
DOI: 10.1177/0361684311434307
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Marital and Partner Relationships in the Aftermath of Hurricane Katrina

Abstract: Little is known about the impact of natural disasters on marital and partner relationships. In this study, the authors aimed to fill this gap by investigating the changes in such relationships in a sample of 40 low-income, mostly African American women who survived Hurricane Katrina. Through in-depth interviews, participants described how the hurricane affected their intimate relationships. The authors found that, although many participants reported negative changes in their relationships, others reported that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 71 publications
6
45
0
5
Order By: Relevance
“…Even among the vulnerable group in the RISK study, there was considerable variation in adaptive resources and psychological responses. We found that perceived social support predisaster protected victims from exposure to disaster‐related stressors and loss (Lowe, Chan, and Rhodes ) as did specific support providers, including intimate partners (Lowe, Rhodes, and Scoglio ). Consistent with the family stress model (Conger et al.…”
Section: Studying Disasters and Their Aftermathmentioning
confidence: 86%
See 1 more Smart Citation
“…Even among the vulnerable group in the RISK study, there was considerable variation in adaptive resources and psychological responses. We found that perceived social support predisaster protected victims from exposure to disaster‐related stressors and loss (Lowe, Chan, and Rhodes ) as did specific support providers, including intimate partners (Lowe, Rhodes, and Scoglio ). Consistent with the family stress model (Conger et al.…”
Section: Studying Disasters and Their Aftermathmentioning
confidence: 86%
“…For example, when qualitative data revealed that some women experienced the hurricane as a positive force, leading them to break the hold of friends and family interfering with their education and social mobility (Lowe et al. ), we added measures of posttraumatic growth (PTG) and social networks to the subsequent survey (Lowe, Manove, and Rhodes ). We realized we had been framing all of our survey questions around the negative consequences of the disaster.…”
Section: Studying Disasters and Their Aftermathmentioning
confidence: 99%
“…Acute and chronic stressors put parents and children at risk for experiencing psychological as well as relational problems. For instance, individuals report similar symptoms of distress (e.g., hopelessness; anxiety; frustration) in response to natural disasters 2 , caring for an aging parent or child with special needs 3,4 , neighborhood disorder 5 , and acculturative stress 6 , to name a few. Over time, personal distress may strain family relationships and disrupt parenting, eventually threatening the health and wellbeing of children living in the home.…”
Section: Family Stress Model Review 3 Stress and Child Development: Amentioning
confidence: 99%
“…Racial and ethnic minorities and impoverished populations tend to face the greatest challenges securing stable housing following a disaster, in part due to the intersection of these two axes of inequality. Lower‐income disaster survivors often end up staying with family or friends, and/or doubling up with other survivors (Lowe, et al ; Morrow ; Reid ; Weber and Peek ), creating cramped and potentially stressful living conditions. After Hurricane Andrew, rental units in minority neighborhoods recovered more slowly than those in non‐minority neighborhoods, in part due to a lack of disaster‐specific housing and planning policies (Zhang and Peacock ).…”
Section: Recent Research On Inequalities and Disastermentioning
confidence: 99%